2014
DOI: 10.1155/2014/728254
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Evaluation of the Mixture Toxicity of Twelve Phenols and Ten Anilines to the Freshwater PhotobacteriumVibrio qinghaiensissp.-Q67

Abstract: Twelve substituted phenols and ten substituted anilines were chosen to investigate if the dose addition and independent action models can be used to evaluate the mixture toxicity of phenolic and aniline derivatives (PADs). Their photobacterium toxicity to the freshwater luminescent bacteriumVibrio qinghaiensissp.-Q67 showed that the two-parameter Weibull or Logit function could be effectively applied to describe the dose-response relationships. The joint toxicity of three equivalent-effect concentration ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In the present study, the toxicity of a petroleum hydrocarbon mixture of F2 (C10-C16) and F3 (>C16-C34) petroleum hydrocarbons to soil invertebrates fit models of similar or dissimilar mechanisms of action equally well, despite the consensus that petroleum hydrocarbons have similar modes of action. Other studies on toxicants with similar and dissimilar mechanisms of action found comparable results, that is, independent action and concentration addition fit observed mixture toxicity data similarly (Faust et al 1994;Backhaus et al 2004;Cedergreen et al 2008;Mo et al 2014;Schnug et al 2014;Qiu et al 2016). Of the limited studies on binary petroleum hydrocarbon mixture toxicity to soil invertebrates, Cermak et al (2013) found that mixtures of F2 and F3 petroleum hydrocarbon followed concentration addition based on earthworm organism tissue concentration.…”
Section: Mixture Toxicitymentioning
confidence: 86%
“…In the present study, the toxicity of a petroleum hydrocarbon mixture of F2 (C10-C16) and F3 (>C16-C34) petroleum hydrocarbons to soil invertebrates fit models of similar or dissimilar mechanisms of action equally well, despite the consensus that petroleum hydrocarbons have similar modes of action. Other studies on toxicants with similar and dissimilar mechanisms of action found comparable results, that is, independent action and concentration addition fit observed mixture toxicity data similarly (Faust et al 1994;Backhaus et al 2004;Cedergreen et al 2008;Mo et al 2014;Schnug et al 2014;Qiu et al 2016). Of the limited studies on binary petroleum hydrocarbon mixture toxicity to soil invertebrates, Cermak et al (2013) found that mixtures of F2 and F3 petroleum hydrocarbon followed concentration addition based on earthworm organism tissue concentration.…”
Section: Mixture Toxicitymentioning
confidence: 86%
“…Considering the simplicity ease to utilization, TU based on the CA model has been used in the context of unknown toxic effects of a single component. There are partly researches were implemented to investigate the feasibility of CA and IA (Zhang et al, 2008;Liu et al, 2009;Zhou et al, 2010;Mo et al, 2014;Villa et al, 2014;Tong et al, 2015). It is not to say, CA (or IA) is only propitious to the similar (dissimilar) toxicology modes of action.…”
Section: Independent Action Methodsmentioning
confidence: 99%
“…There are partly researches were implemented to investigate the feasibility of CA and IA (Zhang et al, 2008 ; Liu et al, 2009 ; Zhou et al, 2010 ; Mo et al, 2014 ; Villa et al, 2014 ; Tong et al, 2015 ). It is not to say, CA (or IA) is only propitious to the similar (dissimilar) toxicology modes of action.…”
Section: Methods Of Concentration Addition and Independence Actionmentioning
confidence: 99%
“…Mo et al [39] employed mixtures of 22 phenolic and aniline derivatives (PADs) to investigate if the dose addition and independent action models can be used to evaluate their toxicity. A mixture’s photobacterium toxicity to the Vibrio qinghaiensis sp.…”
Section: Successful Application Of Computational Modeling For Predmentioning
confidence: 99%